Orientalism - Said, Edward W (Penguin Books, 2019)
A groundbreaking critique of the West's historical, cultural, and political perceptions of the East that is—three decades after its first publication—one of the most important books written about our divided world. "Intellectual history on a high order ... and very exciting." —The New York Times In this wide-ranging, intellectually vigorous study, Said traces the origins of "orientalism" to the centuries-long period during which Europe dominated the Middle and Near East and, from its position of power, defined "the orient" simply as "other than" the occident. This entrenched view continues to dominate western ideas and, because it does not allow the East to represent itself, prevents true understanding. Source: Publisher
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Afrique (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Control mapping: Peter Pitseolak and Zacharias Kunuk on reclaiming Inuit photographic images and imaging - Winfield, Norman David (Decolonization: Indigeneity, Education & Society, 2014)
Inuit have been participating in the development of photo-reproductive media since at least the 19th century, and indeed much earlier if we continue on Michelle Raheja’s suggestion that there is much more behind Nanook’s smile than Robert Flaherty would have us believe. This paper examines how photographer Peter Pitseolak (1902-1973) and filmmaker Zacharias Kunuk have employed photography and film in relation to Raheja’s notion of “visual sovereignty” as a process of infiltrating media of representational control, altering their principles to visualize Indigenous ownership of their images. For camera-based media, this pertains as much to conceptions of time, continuity and “presence,” as to the broader dynamics of creative retellings. This paper will attempt to address such media-ontological shifts – in Pitseolak’s altered position as photographer and the effect this had on his images and the “presence” of his subjects, and in Kunuk’s staging of oral histories and, through the nature of film as an experience of “cinematic time,” composing time in a way that speaks to Inuit worldviews and life patterns – as radical renegotiations of the mediating properties of photography and film. In that they displace the Western camera’s hegemonic framing and time-based structures, repositioning Inuit “presence” and relations to land within the fundamental conditions of photo-reproduction, this paper will address these works from a position of decolonial media aesthetics, considering the effects of their works as opening up not only for more holistic, community-grounded representation models, but for expanding these relations to land and time directly into the expanded sensory field of media technologies.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé